Risk factors and outcomes associated with the carriage of tigecycline- and vancomycin-resistant Enterococcus faecium. Issue 2 (February 2021) - Kessel, Johanna; Bender, Jennifer; Werner, Guido; Griskaitis, Matas; Herrmann, Eva; Lehn, Annette; Serve, Hubert; Zacharowski, Kai; Zeuzem, Stefan; Vehreschild, Maria J.G.T.; Wichelhaus, Thomas A.; Kempf, Volkhard A.J.; et al.
Highlights: ■ Identification of tigecycline exposure as the main risk factor for the emergence of vancomycin and tigecycline resistant enterococci (TVRE). ■ Clinical characterization of a large cohort of TVRE patients showed that bloodstream-infection with TVRE is associated with worse clinical outcome. ■ Whole genome sequencing helps to detect transmission routes of TVRE. ■ Antimicrobial stewardship and infection control interventions are appropriate to prevent the emergence and spread of TVRE. Summary: Objectives: Vancomycin-resistant E. faecium (VRE) is a common cause of healthcare-associated infections. The emergence of VRE with tigecycline resistance (TVRE) is increasing but its impact on patient outcome is still not well defined. This study aimed to assess risk factors for the acquisition of TVRE and of patient outcomes associated with TVRE carriage/infection. Methods: At the University Hospital Frankfurt, we conducted a matched pair TVRE-VRE analysis to identify risk factors for TVRE carriage. Bed-to-bed contacts and potential transmission routes were reconstructed. TVRE were whole-genome sequenced to confirm suspected transmission events and to identify tigecycline resistance mechanisms. Results: 76 TVRE cases were identified between 02/2014–04/2017 and compared to VRE colonized or infected controls. TVRE carriage was associated with exposure to tigecycline, an increased rate of bloodstream infections (BSI) with VRE or Candida spp., and higher mortality. Whole-genome sequencing-based analysis of 24 TVRE provided evidence for transmissions of TVRE, also across different wards. Conclusions: Tigecycline exposure is the main risk factor for TVRE carriage. VRE/TVRE- and Candida -BSI are associated with worse clinical outcome. Hospital transmission of TVRE may occur despite strict contact precautions, whereas both antimicrobial stewardship and infection control interventions are of high importance to prevent emergence and spread of TVRE.